PENGARUH HbA1c TERHADAP SINDROMA MATA KERING PADA PASIEN DIABETES MELLITUS DI SURABAYA - NI WAYAN WIWIN OKTORI; VARIDIANTO YUDO TJAHJONO; SRI ARIANI (HANG TUAH MEDICAL JOURNAL, 2020)
Abstract Background: Diabetes mellitus is a public health problem experienced by many countries and becomes a serious problem, affecting health in the world. Various complications of DM related to the surface of the eye is dry eye syndrome. Dry eye syndrome is an eye disorder with symptoms of discomfort, pain, dryness and foreign body sensation in the eye. The level of glycosylated hemoglobin (HbA1c) is one indicator of DM and it is stated that the prevalence of dry eye syndrome is significantly higher in DM sufferers than in healthy individuals. The Aim of this study to know the effect of HbA1c on dry eye syndrome in patients with diabetes mellitus Method :. This study used a cross sectional method and the sampling method used was purposive sampling. Samples taken as many as 34 people are patients with diabetes mellitus aged 18-55 years who have HbA1c results seen from medical records at the Public Health Center Jagir Surabaya. The research data was taken using the Dry Eye Questionnaire (DEQ), interviews and Schirmer Test I. The research data was then analyzed using a contingency test. Result: The significance value of the HbA1c test with the Schirmer I Test showed p = 0.026; that’s means a significant effect between HbA1c levels on dry eye syndrome with the Schirmer I Test and the significance value of the HbA1c test with the DEQ questionnaire shows p <0.001; that’s means a significant effect between HbA1c levels on dry eye syndrome and DEQ questionnaire, performed on patients with diabetes mellitus in Jagir Health Center, Surabaya City Conclusion: There is an influence of HbA1c levels on dry eye syndrome